Illocutionary Act in To All the Boys Always and Forever movie by Michael Fimognari: Pragmatics Study - Cindya Fatharani Hasya Putri; Hendar Hendar (Budapest International Research and Critics University, 2022)
This study aimed to explain the types of Illocutionary Acts in “To All The Boys Always and Forever” dialogue movie and also to determine the context of the situation that supports revealing the intended meanings to explain each type of illocutionary act in the movie with the function of illocutionary itself. This research used the descriptive qualitative research method. The theory used in this study is the theory stated by Searle and Austin to identify the types of illocutionary speech acts and intended illocutionary meaning-based study on Critical Pragmatics book by Kepa Korta and John Perry. There are 71 utterances contained in the illocutionary act from the dialogue’s movie, and the data were classified into five; 18 representatives (25,4%), 17 directive (23,9%), 8 commissive (11,3%), 7 declarative (9,9%), 21 expressive (26,6%). The intended illocutionary meanings found in this research data are stating, claiming, advising, commanding, promising, offering, pronouncing, deciding, praising, and the last is blaming.